Roman Goddess Flora - Ghosh, Ayan (Jio Institute, 2023)
The Flora Fountain was designed and executed entirely in England and transported via ship to India. The fountain is named after Flora, the Roman goddess of flowers and the season of spring. The statue of the goddess stands atop the fountain.